ANALISIS PENGEMBANGAN SEKOLAH HIJAU (GREEN SCHOOL) DAN SEKOLAH SEHAT (HEALTHY SCHOOL) PADA SMPN 1 LUBUK BATU JAYA KABUPATEN INDRAGIRI HULU RIAU - Diana Novitasari; Zulfan Saam; Elda Nazriati (Program Pascasarjana Universitas Riau, 2015)
Pre survey results at several junior high schools in Indragiri Hulu show that theschools were lack of knowledge and awareness on a green and healthy school.Besides, the lack of attention and support from related parties such as health andeducation agencies in providing information, promotion and motivation for theimplementation of green school and the healthy school. The research was conductedfrom May to November 2014 that aimed to analyze the knowledge and attitude of theschool community as well as the development of green school and healthy school injunior high schools in Lubuk Batu Jaya sub district Indragiri Hulu district RiauProvince. The research was conducted using a survey method for the implementation ofgreen school and healthy school. Data collection techniques were observation,questionnaires and interviews. Analysis of quantitative and qualitative data. The resultsobtained from this research were that junior high schools community in Lubuk BatuJaya sub district Indragiri Hulu district Riau province have a high knowledge andgood attitude towards the development of a green school and healthy school. SMPNegeri 1 of Lubuk Batu Jaya sub district Indragiri Hulu district Riau Province has notmet the criteria of green school development program and healthy school.